PENGUASAAN KALIMAT BAHASA INDONESIA MURID PAUD DI KECAMATAN TAMALANREA KOTA MAKASSAR: KAJIAN TRANFORMASI GENERATIF - Kaharuddin, Mutahharah Nemin; Darwis, Muhammad; Usman, Moses (JURNAL ILMU BUDAYA, 2019)
This research aims to analyze a single sentence of Indonesian Language mastery of Paud student in district Tamalanrea Makassar city and  analyze the compound sentence mastery Indonesian Language Paud students in district Tamalanrea city of Makassar. This descriptive study using Generative Transformation approach. The data of this research in the form of a single sentence and sentence compound diujarkan Paud studentss in district Tamalanrea city of Makassar. Method used, i.e. methods refer to the method and ably. The technique used on the method refer to the technique of elisitasi, i.e., while the techniques used in the method of recording techniques, namely, ably and noted. The results of this research show that the Paud students sentence consists of two types of sentences, i.e. a single compound sentence and sentence. Transformation of single sentences, among others, the transformation of addition, subtraction, the turn, and permutasian, the merger of the two processes of transformation, and the transformation process of the four. Compound sentences Paud studentss in district of Tamalanrea, i.e. the compound sentences and compound sentences koordinatif subordinatif. Koordinatif compound sentences based on the relationship of contradiction between clauses and additive compound sentences while subordinatif based on a relationship of causation, agricultural, suppositions, and advanced.